Effect of Partitioning of Nitrogen and Potash Fertilizers on Growth, Yield and Quality of Three Corn Cultivars (Zea mays L.) - Fakhradeen A.Q. Sedeeq; Abeer Yaseen Mohammad (Mesopotamia Journal of Agriculture)
A field experiment was conducted In two locations at fall season 2008, first was in the fields of college of Agriculture - Tikrit University, and the second was in Abu siffa_ Ishaqi. The objective was to assess response of three varieties of corn (Bohoth 106, Eba 5012 and Almesara) to the dates of partitioning of nitrogen (N) and potash (K) fertilizer in four dates, first application of All the amount of (K) before planting and 50% of the (N) at planting and 50% when the plant reach 20 - 25 cm of height. The second was application of 50% of (N) and (K) at planting and 50% when the plant reach 20 - 25 cm, the third was application of 50% of (N) and (K) at planting and the rest 50% at the beginning of inflorescence emergence note, the fourth was application of 25% of (N) and (K) at planting and 50% when the plant reach 20 - 25 cm, while the rest of 25% was applied at the beginning of inflorescence emergence note. Randomized completed block design (RCBD) was used with three replicates. Results of the first location showed superiority of Almesara variety at the first, third and fourth dates of partitioning on the attributes, leaf area index, percentage of fertility, ear diameter and dry weight yield. Bohoth 106 was superior at the first date of partitioning on attributes, ear height, number of leaves of the plant, While Eba 5012 was superior at the second date of partitioning in dry weight yield. Results of the second location showed superiority of Almesaea at the fourth date of partitioning in leaf area index, and Bohoth 106 was superior at the first and third dates in height and number of leaves of plant, while Eba 5012 was superior at the fourth date of partitioning in percentage of lodging plants.